Perbandingan Wasiat dalam Perspektif Kompilasi Hukum Islam (KHI) dan Burgerlijk Wetboek (BW) - Moh. Syamsul Mu'arif (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2015)
Testament is one of the aspects of civil law which belongs to Islamic marriage laws. On social issues, the problems will not be underestimated as a social construct that maps the public perception of religious and nationalist groups. Government officials administering the State provide a solution in the form of implementation of the postulate of the will in the presence of Burgerlijk Wetboek (BW) as a guideline Kompilasi Islamic Law (KHI) to guide religious groups. Charge two guidelines and be appreciated by pros and cons in the social domain. By considering several postulations texts and findings of thought in both the conservative position, modern or liberal, can find common ground that can be justified academically in relation to maqâs?id Syarî’ah. In comparative studies, social of mas?lah?ah match point which can be used as a guide for each group. This study concluded that there was no significant difference in the two postulations. This is evidenced in the level of definition, limits will part as well as the validity and cancellation will. Thus, according to the researchers, the application will be it based on the postulation BW and KHI, is still based on the social good.